2021
DOI: 10.1111/sltb.12777
|View full text |Cite
|
Sign up to set email alerts
|

Defeat, entrapment, and suicidal ideation: Twelve‐month trajectories

Abstract: Background: Defeat and entrapment have been highlighted in the development of suicidal ideation within the Integrated Motivational-Volitional model of suicidal behavior. Research suggests that entrapment has to be differentiated into internal and external entrapment. The aim of this study was to investigate the associations between defeat, internal, external entrapment, and suicidal ideation within and prospectively over measurements. Methods: A sample of 308 psychiatric inpatients (53% female) aged 18 to 81 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 54 publications
4
19
1
1
Order By: Relevance
“…PTSD and its associated symptoms may serve as persistent risk factors for the emergence of SI when the individual endeavors to “escape from the aversive psychological states that characterize PTSD” (Bryan, 2016, p. 2). Indeed, both Höller et al (2021) and Rasmussen et al (2010) demonstrate the mechanistic properties of IE and not EE in predicting SI in the context of defeat and suggest that the deleterious effects of IE may be more resistant to intrapersonal change whereas changes in EE are subject to greater intrapersonal locus of control.…”
Section: Discussionmentioning
confidence: 99%
“…PTSD and its associated symptoms may serve as persistent risk factors for the emergence of SI when the individual endeavors to “escape from the aversive psychological states that characterize PTSD” (Bryan, 2016, p. 2). Indeed, both Höller et al (2021) and Rasmussen et al (2010) demonstrate the mechanistic properties of IE and not EE in predicting SI in the context of defeat and suggest that the deleterious effects of IE may be more resistant to intrapersonal change whereas changes in EE are subject to greater intrapersonal locus of control.…”
Section: Discussionmentioning
confidence: 99%
“…We asked our respondents—all of whom reported having used alcohol, opioids, or psychostimulants in the previous six months—about introversion, changes in drug use during the pandemic, and changes in their sense of entrapment . Entrapment is a feeling of being unable to escape internal and/or external stressors and has been linked to depression and suicidal behavior ( Carvalho et al, 2021 ; Gilbert & Allan, 1998 ; Höller et al, 2021 ; Stenzel et al, 2020 ). Increased entrapment seems likely to result from a mismatch between social preferences and social circumstances—and might plausibly cause more drug use.…”
Section: Introductionmentioning
confidence: 99%
“…The explained variance in suicidal ideation through internal entrapment is smaller, which emphasizes the role of internal entrapment especially for the development of hopelessness and not to such a large amount of suicidal ideation, which is in line with the high correlations we found for hopelessness and internal entrapment. Earlier studies [ 12 , 13 ] finding effects for associations between internal entrapment and suicidal ideation did not consider hopelessness, which might explain these effects.…”
Section: Discussionmentioning
confidence: 98%
“…This study aimed at examining the differential relation between internal and external entrapment and suicidal ideation and investigated whether this relation is (partially) mediated by hopelessness. Prior studies showed that internal entrapment might be more important than external entrapment in the development of suicidal ideation [ 12 , 13 ]. However, it has not yet been examined why this might be the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation